Regulatory Harmonization in Healthcare Services and the Implementation of Pancasila Values in the National Health Insurance Era - Emirza Nur Wicaksono; Dian Ratu Ayu Uswatun Khasanah; Ronald Jolly pongantung (Pancasila: Jurnal Keindonesiaan, 2026)
This study aims to analyze the harmonization of healthcare legislation with Pancasila values within the context of the National Health Insurance (Jaminan Kesehatan Nasional/JKN) system in Indonesia. Within the framework of the Indonesian rule of law, Pancasila functions not only as the state’s foundational ideology but also as a fundamental norm (grundnorm) that should guide all legal regulations, including those in the health sector. This research employs a normative legal method using statutory, conceptual, and philosophical approaches. The findings indicate that, at the normative level, JKN regulations have incorporated key Pancasila values such as social justice, humanity, unity, and deliberation; however, various forms of disharmony—both substantive and regulatory, as well as horizontal and vertical—remain evident. Moreover, the implementation of these regulations has not fully reflected the substantive and ideological principles of Pancasila, as shown by regulatory inconsistencies, overlapping policies, and structural constraints that indicate weak integration of core values in healthcare governance. Therefore, this study proposes a harmonization model that goes beyond technical and formal alignment by embedding Pancasila-based legal ethics through legislative review, institutional strengthening, public participation, ideological education for healthcare professionals, and independent oversight, in order to ensure that the JKN system functions effectively as an instrument of social justice and the protection of human rights.